2011
DOI: 10.1021/ic202058h
|View full text |Cite
|
Sign up to set email alerts
|

A Thiophosphinidene Complex as a Vehicle in Phosphinidene Transmetalation: Easy Formation and Cleavage of a P–S Bond

Abstract: A method for the generation of transition metal-phosphorus multiple bonds has been developed using the reactions of a novel thiophosphinidene-bridged dimolybdenum complex with different metal carbonyls. The overall process could be considered as a transmetalation of the phosphinidene ligand involving the activation of P-S and P-Mo bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Then it can be concluded that the geometrical constrains imposed by the bifunctional PMes* and PC 5 H 4 phosphinidenes are a critical element enabling partial delocalisation of the π-bonding interaction over the MPM skeleton in these complexes. Indeed, the same structural effect was later observed for the MPM´ skeletons in the heterometallic complexes 71, 72 and 73, with long PMo bonds of only 2.33 Å [74]. [Sc2L2{μ-P(C6H3Me2)}{μ-η 2 :η 2 - …”
Section: Asymmetric Trigonal Planar Phosphinidene Complexessupporting
confidence: 61%
See 2 more Smart Citations
“…Then it can be concluded that the geometrical constrains imposed by the bifunctional PMes* and PC 5 H 4 phosphinidenes are a critical element enabling partial delocalisation of the π-bonding interaction over the MPM skeleton in these complexes. Indeed, the same structural effect was later observed for the MPM´ skeletons in the heterometallic complexes 71, 72 and 73, with long PMo bonds of only 2.33 Å [74]. [Sc2L2{μ-P(C6H3Me2)}{μ-η 2 :η 2 - …”
Section: Asymmetric Trigonal Planar Phosphinidene Complexessupporting
confidence: 61%
“…The above reaction seems to be a characteristic feature of asymmetric trigonal planar phosphinidene and Te) [111,74]. The main products obtained in all reactions were complexes of type 188 displaying three-membered MoPZ cycles (Scheme 92).…”
Section: Scheme 91mentioning
confidence: 88%
See 1 more Smart Citation
“…1) was described in our preliminary report on this chemistry, 9 and will be only briefly discussed here. 1) was described in our preliminary report on this chemistry, 9 and will be only briefly discussed here.…”
Section: Structure Of Compoundmentioning
confidence: 99%
“…9 It was thus of interest to further explore this sort of reaction as a synthetic route to heterometallic phosphinidene-bridged derivatives. 9 It was thus of interest to further explore this sort of reaction as a synthetic route to heterometallic phosphinidene-bridged derivatives.…”
Section: Introductionmentioning
confidence: 99%